Effectiveness of the participation of the victims of the armed conflict in the design, execution and control of public policies. - Umbarila Romero, Mauricio; Guzmán Gómez, Angie Steffany (Universidad Pedagógica y Tecnológica de Colombia, 2021)
In order to develop this article, the starting point was its contextualisation as it concerns the participation of the victims of the armed conflict in Colombia in the Public Policy (Law 1448 of 2011), which is why it was approached from a universal and general perspective of public policies, observing with special care their definition, structure, phases, intervening parties and opponents, as well as their sequential model, in order to - in this way - demonstrate the participation that must exist on the part of the population at which they are aimed, emphasising the key role of the ruling elites and determining what differentiates them from the dominant ones. To this end, allusion was made to the successes and failures of the national government in its design, execution and control, referring to the previous stages that were exhausted at the normative and practical levels. This will allow us, at the end of the exercise and in a deductive manner, to consider the effectiveness of victims' participation in the construction of joint actions in the National System of Attention and Comprehensive Reparation for Victims.